Chlorogenic acid inhibits cholestatic liver injury induced by α-naphthylisothiocyanate: involvement of STAT3 and NFκB signalling regulation. (1st July 2016) - Tan, Zhen; Luo, Min; Yang, Julin; Cheng, Yuqing; Huang, Jing; Lu, Caide; Song, Danjun; Ye, Meiling; Dai, Manyun; Gonzalez, Frank J; Liu, Aiming; Guo, Bin
Abstract: Objectives: Chlorogenic acid (CGA) is one of the most widely consumed polyphenols in diets and is recognized to be a natural hepatoprotective agent. Here, we evaluated the protective effect and the potential mechanism of CGA against ɑ-naphthylisothiocyanate (ANIT)-induced cholestasis and liver injury. Methods: Twenty-five male 129/Sv mice were administered with CGA, and ANIT challenge was performed at 75 mg/kg on the 4th day. Blood was collected and subjected to biochemical analysis; the liver tissues were examined using histopathological analysis and signalling pathways. Key findings: Chlorogenic acid almost totally attenuated the ANIT-induced liver damage and cholestasis, compared with the ANIT group. Dose of 50 mg/kg of CGA significantly prevented ANIT-induced changes in serum levels of alanine aminotransferase, alkaline phosphatases, total bile acid, direct bilirubin, indirect bilirubin (5.3-, 6.3-, 18.8-, 158-, 41.4-fold, P<0.001) and aspartate aminotransferase (4.6-fold, P<0.01). Expressions of the altered bile acid metabolism and transport-related genes were normalized by cotreatment with CGA. The expressions of interleukin 6, tumour necrosis factor-α and suppressor of cytokine signalling 3 were found to be significantly decreased (1.2-fold, ns; 11.0-fold, P<0.01; 4.4-fold, P<0.05) in the CGA/ANIT group. Western blot revealed that CGA inhibited the activation and expression of signal transducer and activator of transcription 3 and NFκB. Conclusions: These data suggest that CGA inhibits both ANIT-induced intrahepatic cholestasis and the liver injury. This protective effect involves down-regulation of STAT3 and NFκB signalling.